Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fpubh.2022.952858
|View full text |Cite
|
Sign up to set email alerts
|

The effect and mechanism of Internet use on the physical health of the older people—Empirical analysis based on CFPS

Abstract: The use of the Internet has a promoting effect on the physical health of the older people. However, previous studies are mostly focused on the perspective of the overall population, or limited to the direct effects, ignoring the exploration of the mechanism of action and the perspective of the older people. Based on the data of the China Family Panel Survey (CFPS) in 2014, 2016, 2018, and 2020, this study found that the use of the Internet has a significant effect on the physical health of the older people, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…However, the Internet use (frequency of Internet use) of different older groups with varying individual characteristics is heterogeneous is notable. Previous studies have demonstrated the impact of Internet use (frequency of Internet use) on depression across various demographic groups [ 44 , 48 , 49 ], which differ in terms of income level, gender, education level, age, and number of accompanying persons [ [50] , [51] , [52] ]. However, limited evidence exists regarding the differences observed among groups based on their physical health status or living arrangements.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Internet use (frequency of Internet use) of different older groups with varying individual characteristics is heterogeneous is notable. Previous studies have demonstrated the impact of Internet use (frequency of Internet use) on depression across various demographic groups [ 44 , 48 , 49 ], which differ in terms of income level, gender, education level, age, and number of accompanying persons [ [50] , [51] , [52] ]. However, limited evidence exists regarding the differences observed among groups based on their physical health status or living arrangements.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the mechanism of the association between the frequency of Internet use and incident disability among older people, in addition to the forementioned mental health aspect, we have two possible explanations. First, a previous study from China reported that Internet use by older adults increased their exercise frequency, resulting in improved physical health status [ 39 ]. In Japan, during the COVID-19 pandemic, in order to prevent a decline in physical strength due to lockdown restrictions, academic societies and local governments have created exercise videos that older people can do at home and applications that allow older people to exercise while self-managing online, and have released them on the Internet [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its samples cover 25 provinces/cities/autonomous regions in China. CFPS collects data from three dimensions: individual, family, and community, and adopts various forms of questionnaires such as long, short, pick-up, and telephone interviews, aiming to reflect the development and changes in China’s society, economy, population, health and education 15 . The CFPS did not investigate smoking behavior among children and adolescents aged 15 years and younger, so data from this population were excluded from this study, and 34,743 data were obtained.…”
Section: Methodsmentioning
confidence: 99%